2018
DOI: 10.18203/issn.2454-5929.ijohns20182948
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of hearing loss by pure tone audiometry in chronic suppurative otitis media patients

Abstract: <p class="abstract"><strong>Background:</strong> Hearing loss associated with the CSOM affects the patients’ communication with others and results in poor quality of life. Degree and type of hearing loss can be assessed by pure tone audiometry, which helps in predicting the status of tympanic membrane, ossicular chain, and inner ear and also helps in preoperative planning.</p><p class="abstract"><strong>Methods:</strong> Patients with CSOM aged 10 years and above were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…Likewise, the audiometric testing results classified by the disease activity are consistent with previous literature that suggests a mild to moderate conductive hearing loss in patients with COM [37][38][39]. Moreover, previous reports describe an air-bone gap secondary to conductive hearing loss as a common finding in COM patients [37].…”
Section: Plos Onesupporting
confidence: 90%
“…Likewise, the audiometric testing results classified by the disease activity are consistent with previous literature that suggests a mild to moderate conductive hearing loss in patients with COM [37][38][39]. Moreover, previous reports describe an air-bone gap secondary to conductive hearing loss as a common finding in COM patients [37].…”
Section: Plos Onesupporting
confidence: 90%
“…This study highlighted the importance of PTA in identifying the sensorineural component in patients with CSOM. 8 Maeda Y et al found in their study among older Japanese patients that thresholds on the PTA is a good predictor of speech perception by speech audiometry among older persons, which could provide clinically important information for hearing aid fitting and cochlear implantation. 9 Devashri UP and others in their study on correlation of PTA findings with intraoperative findings in patients with Chronic Suppurative Otitis Media did not find the air conduction thresholds or the air-bone gap in PTA as a reliable factor to predict the intra operative ossicular status.…”
Section: Introductionmentioning
confidence: 96%
“…Chronic suppurative otitis media (CSOM) is one of the most common otolaryngological diseases with a wide range of prevalence from 0.5% to 33.3% in both developing and developed countries (1)(2)(3). CSOM is defined as inflammation of the middle ear cavity, eustachian tube, and mastoid air cell system caused by aerobic and anaerobic bacteria (4), leading to typical irreversible tympanic membrane perforation, which presents with ear discharge (5).…”
Section: Introductionmentioning
confidence: 99%